Tematizando as lutas na educação física escolar: relato de uma prática pedagógica no contexto do PIBID - Marlon Messias Santana Cruz; Abília Ana Castro Neta; Drieli Fernandes Boa Sorte; Joice Tainá de Jesus Santos; Ana Gabriela Alves Medeiro (Universidade Estadual do Oeste do Paraná, 2018)
This study was developed within the scope of the Institutional Scholarship Initiative Program in the context of the subproject "Physical School Education: building pedagogical possibilities from a cultural perspective" of the undergraduate course in Physical Education of the University of the State of Bahia (UNEB) - Campus XII. The pedagogical actions were carried out in a public elementary school located in the municipality of Guanambi-Ba, from March to November 2017. The information needed to elucidate the research problem was produced in the context of pedagogical intervention and Later systematized and analyzed. This information was collected through reflective records - or daily logs - carried out daily, in which details related to the development of the classes were transcribed. It was also used, as a source for obtaining the results, the audio recording of discussions and talk wheels. From the developments resulting from the problematizations and the evaluation carried out at the end of the school year, we identified in the students a possible deconstruction of the representations or signs of the dominant culture, initially present in their discourses. In the end, we identified, from the problematizations and experiences, that some stereotyped discourses about the struggles were destabilized.